Access to colposcopy in the State of São Paulo, Brazil: probabilistic linkage study of administrative data - Lewis Fletcher Buss; Lise Cury; Caroline Madalena Ribeiro; Gulnar Azevedo e Silva; José Eluf Neto (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
Cervical cancer screening is a multistage process, therefore access to both the primary test and subsequent diagnostic procedures is essential. Considering women undergoing screening on the public health system in the State of São Paulo, Brazil, we aimed to estimate the proportion of women accessing colposcopy within six months of an abnormal smear result. We retrieved records from two administrative databases, the Information System on Uterine Cervical Cancer (SISCOLO) that contains smear results and the Outpatient Information System of the Brazilian Unified National Health System (SIA/SUS) that records colposcopies. A reference cohort consisted of women, aged 25 years or older, with an abnormal smear result between May 1, 2014, and June 30, 2014. We excluded prevalent cases. We linked the reference cohort and records in the SIA/SUS extending to December 31, 2014. After excluding prevalent cases, 1,761 women with abnormal cytology results were left. A total of 700 (39.8%) women were linked to a colposcopy record within the follow-up period; this dropped to 671 (38.1%) women when follow-up was censored at six months. We could notice a slightly higher attendance in women living in the metropolitan region of São Paulo compared with residents of the rest of the state. We found no association between colposcopy attendance and age or cytology class. These results emphasize that access to colposcopy in the public health system in São Paulo is limited. This compromises the quality of screening, and the issue needs to be prioritized in service planning.